Intervention for Smokers through New Communication Technologies: What Perceptions Do Patients and Healthcare Professionals Have? A Qualitative Study - Trujillo Gómez, Jose Manuel (PLoS One, 2015)
BACKGROUND: The use of information and communication technologies (ICTs) in the health service is increasing. In spite of limitations, such as lack of time and experience, the deployment of ICTs in the healthcare system has advantages which include patient satisfaction with secure messaging, and time saving benefits and utility for patients and health professionals. ICTs may be helpful as either interventions on their own or as complementary tools to help patients stop smoking. OBJECTIVES: To gather opinions from both medical professionals and smokers about an email-based application that had been designed by our research group to help smoking cessation, and identify the advantages and disadvantages associated with interventions based on the utilization of ICTs for this purpose. METHODS: A qualitative, descriptive–interpretative study with a phenomenological perspective was performed to identify and interpret the discourses of the participating smokers and primary healthcare professionals. Data were obtained through two techniques: semi-structured individual interviews and discussion groups, which were recorded and later systematically and literally transcribed together with the interviewer’s notes. Data were analyzed with the ATLAS TI 6.0 programme. RESULTS: Seven individual interviews and four focal groups were conducted. The advantages of the application based on the email intervention designed by our research group were said to be the saving of time in consultations and ease of access for patients who found work timetables and following a programme for smoking cessation incompatible. The disadvantages were thought to be a lack of personal contact with the healthcare professional, and the possibility of cheating/ self-deception, and a greater probability of relapse on the part of the smokers. CONCLUSIONS: Both patients and healthcare professionals viewed the email-based application to help patients stop smoking as a complementary aid to face-to-face consultations. Nevertheless, ICTs could not substitute personal contact in the smoking cessation programme.